ANALYSING TRADE FLOWS AND INDUSTRIAL STRUCTURE OF INDIA: THE QUESTION OF DATA HARMONISATION - Veeramani C (Centre for Development Studies-WP321, 2001)
An important requirement for the analysis of trade flows in relation to domestic industrial structure is the availability of a database covering information on trade flows, industry and firm characteristics. Such a database, as yet, does not exist in India. Thus, one is left to opt for the second best solution of compiling data from different sources to produce a harmonised database. This paper is an attempt to provide guidance in that direction. It raises certain relevant research issues on international trade in relation to domestic industrial structure, attempts a critical assessment of various available data sources for empirical analysis and highlights the advantages of choosing certain specific sources: (i) publications of the Directorate General of Commercial Intelligence and Statistics (DGCI&S) which provide data on India's foreign trade, (ii) Annual Survey of Industries (ASI), which provides data on industry characteristics, and (iii) the electronic data base `Prowess', which provides data on firm characteristics. Following this, the data on trade flows, industry and firm characteristics are sought to be harmonised. First, the DGCI&S data are matched with 3-digit level National Industrial Classification (NIC) in the ASI, using the concordance table prepared by Debroy and Santhanam (1993). Second, we have constructed a concordance table for selected manufacturing sectors wherein the 3-digit items of NIC are matched with the industry categories in Prowess. Its appropriateness is evaluated by comparing data on value of output and total emoluments to employees as reported in ASI with that in Prowess. By and large, it appears that our concordance table is consistent and effective.